PEMANFAATAN MEDIA AUDIO UNTUK MENINGKATKAN KETERAMPILAN MENYIMAK CERITA (LISTERNING) BAHASA INGGRIS BAGI SISWA SMAN 2 PRAYA - Suryatni Suryatni (Jurnal Paedagogy, 2017)
The purpose of this study was to determine the quality of learning listening to English using audio media in Class XI-IIS-1 SMA Negeri 2 Praya. This research method uses a classroom action research method consisting of 2 cycles of action. Each cycle consists of four stages including planning, implementing, observing the results of actions, and reflecting. Based on the results of this study, it can be concluded that the use of audio media can improve listening skills in English in class XI-IIS-1 SMAN 2 Praya, Central Lombok Regency, 2018/2019 academic year. This increase can be seen from the classical completeness obtained in the first cycle of 48.15% and the second cycle increased to 88.89%. This increase can also be seen from the results of observations of teacher activity by 12 in the good category in cycle I and increasing to 17 in the very good category in the second cycle. Meanwhile, student activity in the first cycle was 41 in the active category, increasing to 65 in the very active category in the second cycle. Based on the results of the analysis of cycle I and II, it was obtained an increase in classical completeness by 40.74%.